Projeto de caixa de redução por engrenagens para veículo Baja SAE e impacto da inércia rotacional dos componentes na performance - Cirqueira, Lucca Tardivo (Universidade Federal de São Carlos, 2023)
This work describes the design of a gearbox for a Baja SAE vehicle, for the Baja UFSCar team, and a study to measure the impact of the rotational inertia of the transmission system on the prototype's performance. The gearbox represents the second stage of the transmission, and its function is to complement the first stage, carried out by a CVT (Continuously Variable Transmission), in order to provide enough torque to the wheels so that the vehicle will have the best possible performance and be able to overcome the obstacles present in official SAE (Society of Automotive Engineers) competitions. The objective of this work was to present the developed project of the gearbox of the “M8” prototype, used from 2020 to 2022 by the Baja UFSCar team, highlighting the main considerations made and decisions taken, based on the team's input parameters, limitations, and available resources. The focus was on reducing the mass of components (gears, shafts, housing), aiming to improve the vehicle’s overall performance and outperform its predecessor, the “Moisés” prototype used in 2018 and 2019. The dimensioning of the components was made according to traditional standards and bibliographies, but with a less conservative approach in order to avoid the oversizing that is typical of these methodologies, and also using finite element simulations for optimization. Besides performance, another indicator used to evaluate the evolution of the project was the rotational inertia of the rotating components of the transmission system. The equivalent rotational inertia of the transmission was equated, and converted to an equivalent mass, making it possible to measure its impact on the vehicle's performance. The study showed that the main factor that contributed to the performance increase was the mass reduction of the vehicle as a whole, with the rotational inertia of the components being a secondary factor. In general, the present work achieved its proposed objectives, because even though there are improvements to be made, the gearbox project presented contributed to Baja UFSCar team reaching expressive results in SAE competitions.
Gearbox design for Baja SAE vehicle and inertia impact rotation of the components in the performance
Keywords: Caixa de Redução; Gearbox; Baja; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS